2018
DOI: 10.1055/s-0044-102094
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Potential of Elsholtzia densa Against Acute and Chronic Models of Liver Damage in Wistar Rats

Abstract: The aim of the present study was to evaluate the hepatoprotective activity of methanolic extract of Elsholtzia densa against experimentally induced acute (CCl) and chronic (paracetamol) liver injury in albino wistar rats. Activity was measured by monitoring the serum levels of ALT, ALP AST and LDH, total protein levels, bilirubin and albumin. The results of the CCl and paracetamol-induced liver toxicity experiments showed that the rats treated with the methanolic extract of Elsholtzia densa exhibited a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
1
0
1
Order By: Relevance
“…The improvement of survival rates and attenuation of liver histological damage in APAP-induced liver injury model further validated that SAFE could alleviate liver injury. These results were confirmed by other previous findings, the increase of survival rate, decrease of serum markers, and alleviation of liver histological damage in APAP-induced liver damage after the treatment of different plant extracts [62, 63]. Normally, clinical dose of APAP mainly binds to glucuronic acid or sulfate in the liver and then is excreted into plasma or bile [64, 65].…”
Section: Discussionsupporting
confidence: 87%
“…The improvement of survival rates and attenuation of liver histological damage in APAP-induced liver injury model further validated that SAFE could alleviate liver injury. These results were confirmed by other previous findings, the increase of survival rate, decrease of serum markers, and alleviation of liver histological damage in APAP-induced liver damage after the treatment of different plant extracts [62, 63]. Normally, clinical dose of APAP mainly binds to glucuronic acid or sulfate in the liver and then is excreted into plasma or bile [64, 65].…”
Section: Discussionsupporting
confidence: 87%
“…Pourahmad J et, al. revealed that the hepatotoxicity caused by diclofenac is associated with oxidative stress [13]. On the other hand, liver toxicity decreases with antioxidant compounds, which is another indication of the effect of oxidative stress and free radicals on liver toxicity [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A dose mais utilizada pelos autores foi a de 2.000 mg/kg, representando 26 trabalhos no total de 114, seguido de 1.000 g/kg (21 trabalhos), o gráfico abaixo permite visualizar melhor a distribuição das doses encontradas (Figura 5). A metodologia de indução também foi muito diversificada, desde doses únicas (ELBE et al, 2018) até indução contínua por dias (ZARGAR et al, 2018).…”
Section: Resultsunclassified